The Usability Study Of A Newly Developed Mobile Application Guided Imagery In Indonesian (Gianesia) For Preoperative Patients - Ina Martiana; Achmad Sya'id (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2022)
Patients were commonly feel anxiety before surgical procedure. The anxiety caused by the lack of knowledge or experience in the surgical procedure or safety threats. Guided imagery was a therapy using imagination to overcome the anxiety. Most of the similar apps were provide in English. The aim of this study was to evaluate a mobile app ‘guided imagery in Indonesian (GIANESIA)’ for ease of providing therapy to patients. This study was a quantitative study using descriptive analytical. A total of 6 experts and 41 users were participated in this study. A consecutive sampling was used in this study by criteria inclusion. The experts were given a form to evaluate and users were given a modified questionnaire of system usability scale (SUS). The results shows 97.6% of users was satisfied using the app (mean+SD=83+15.69). All of experts were considered the language in therapy, the appearance of the app, the ease of use, and the content were good. The experts gave suggestions for unseen buttons, lack of information for scoring, unbalanced audio, and confusing in satisfaction message. This GIANESIA app was useful for users with total SUS score >68 which means this app can be used for wider audience. 83.3% of the experts also conclude high satisfaction score >68, so the app and the therapy deserves to be implemented in preoperative patients. This application can be the latest breakthrough to support nursing interventions to make it easier for Indonesia nurses to work. The application improvements need to be made for better quality.